2020
DOI: 10.1016/j.isci.2020.101830
|View full text |Cite
|
Sign up to set email alerts
|

Disturbed Presynaptic Ca2+ Signaling in Photoreceptors in the EAE Mouse Model of Multiple Sclerosis

Abstract: Summary Multiple sclerosis (MS) is a demyelinating disease caused by an auto-reactive immune system. Recent studies also demonstrated synapse dysfunctions in MS patients and MS mouse models. We previously observed decreased synaptic vesicle exocytosis in photoreceptor synapses in the EAE mouse model of MS at an early, preclinical stage. In the present study, we analyzed whether synaptic defects are associated with altered presynaptic Ca 2+ signaling. Using high-resolution immu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
49
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(52 citation statements)
references
References 131 publications
3
49
0
Order By: Relevance
“…For this purpose, we analyzed the length of individual synaptic ribbons of rod photoreceptor synapses in early EAE mice (vs. the control group) by 3D super-resolution structured illumination microscopy (3D SR-SIM) ( Figure 3 ). 3D SR-SIM is particularly useful to examine the contour length ( Figure 1 (A2)) of synaptic ribbons [ 24 , 25 ]. Using 3D SR-SIM, we found that the contour length of photoreceptor synaptic ribbons was significantly smaller in MOG/CFA-injected mice in comparison to CFA-injected control mice on day 9 after injection ( Figure 3 (A1–B2); for quantification, Figure 3 (C1,C2)).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…For this purpose, we analyzed the length of individual synaptic ribbons of rod photoreceptor synapses in early EAE mice (vs. the control group) by 3D super-resolution structured illumination microscopy (3D SR-SIM) ( Figure 3 ). 3D SR-SIM is particularly useful to examine the contour length ( Figure 1 (A2)) of synaptic ribbons [ 24 , 25 ]. Using 3D SR-SIM, we found that the contour length of photoreceptor synaptic ribbons was significantly smaller in MOG/CFA-injected mice in comparison to CFA-injected control mice on day 9 after injection ( Figure 3 (A1–B2); for quantification, Figure 3 (C1,C2)).…”
Section: Resultsmentioning
confidence: 99%
“…Thus, the published functional changes observed on day 9 after injection [ 24 ] correlate with the morphological changes described in the present study. Since a recent study [ 25 ] found alterations of presynaptic Ca 2+ signaling even at earlier time points, i.e., on day 7 and day 8 after injection, we also analyzed mice obtained on day 8 and day 7 after injection for possible defects in synaptic vesicle exocytosis. For this purpose, we monitored synaptic vesicle exocytosis by optical recording of SypHy fluorescence from our transgenic SypHy reporter mice, exactly as previously described [ 24 ], but now on retinal slices obtained from mice on day 8 and day 7 after injection of MOG/CFA (EAE group) or CFA (control group) ( Figure 7 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations